ESSAY: EARLY WARNING - Littell, Franklin Hamlin (Holocaust and genocide studies, 1988)
Genocidal events are not inevitable and can be avoided if illegitimate power groups are prevented from gaining power. A suggested ‘grid’ is presented which will help identify these illegitimate and potentially genocidal movements. There also exists the need to develop Early Waming Systems which will enable us to predict when a society is becoming de-stabilized and approaching the crisis state.